Inhibitor of Differentiation-2 Protein Ameliorates DSS-Induced Ulcerative Colitis by Inhibiting NF-κB Activation in Neutrophils - Jie Ren (Frontiers Media S.A., 2021)
The loss of inhibitor of differentiation-2 (ID2) could lead to the development of colitis in mice, supplementation with exogenous ID2 protein might be a potential strategy to ameliorate colitis. In this study, the effects of ID2 protein supplementation on Dextran sodium sulfate (DSS)-induced colitis were investigated. Firstly, we confirmed that the expression of ID2 was reduced in the colon tissues of DSS-induced colitis mice and patients with ulcerative colitis (UC). Then, we constructed a recombinant plasmid containing the human Id2 gene and expressed it in Escherichia coli (E. coli) successfully. After purification and identification, purified hID2 could ameliorate DSS-induced colitis efficiently in mice by improving disease symptoms, decreasing the levels of proinflammatory cytokines in colon tissues, maintaining the integrity of intestinal barrier and reducing the infiltration of neutrophils and macrophages in the colon. Further study showed that hID2 could be endocytosed efficiently by neutrophils and macrophages, and hID2 lost its protection function against colitis when neutrophils were depleted with an anti-Gr-1 antibody. hID2 decreased the mRNA levels of IL-6, IL-1β and TNF-α in lipopolysaccharides (LPS)-stimulated neutrophils and efficiently inhibited the activation of NF-κB signalling pathway in neutrophils. Interestingly, hID2 showed a synergistic role in inhibition of NF-κB activation with pyrrolidine dithiocarbamic acid (PDTC), an inhibitor of NF-κB activation. Therefore, this study demonstrated the potential use of hID2 to treat UC, and hID2 protein might be a promising anti-inflammatory agent that targets the NF-κB signalling pathway in neutrophils.